1986
DOI: 10.1002/pssa.2210970127
|View full text |Cite
|
Sign up to set email alerts
|

crystal structure, absorption, luminescence properties, and stimulated emission of Ga gehlenite (Ca2–xNdxGa2+xSi1–xO7)

Abstract: Full concentration series of tetragonal melilite‐like Ca2−xNdxGa2+xSi1−xO7 single crystals with desordered structure are grown using Czochralski technique and their precies X‐ray structural analysis is carried out. Intensity, absorption, and luminescence characteristics including orientational ones of Nd2+ ions in Ca2Ga2SiO7 are investigated. Using conventional lamp‐pumping technique pulse stimulated emission at the wavelengths of two channels (4F3/2 → 4I11/m, 13/2) is excied and investigated both, at low and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
79
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 15 publications
1
79
0
Order By: Relevance
“…Until now, only some chalcogenides with chalcopyrite structure [24][25][26] and the organic salt potassium trihydrogen di(cis-4-cyclohexene-1,2dicarboxylate) dihydrate [27] were reported to behave correspondingly. As a consequence of the small birefringence, however, phase matching conditions cannot be fulfilled for χ (2) -based frequency conversion processes, such as second harmonic generation or sum frequency generation. Figure 6 (online color at www.lphys.org) Fragments of SRS and RFWM spectra of our crystal of Sr2ZnGe2O7, recorded at room temperature with picosecond pumping at the wavelength λ f 1 = 1.06415 μm in excitation geometry: (a) (e 1 +e 2 )[(-e 1 +e 2 )(-e 1 +e 2 )] (e 1 +e 2 ); (b) e 3 [(-e 1 +e 2 )(-e 1 +e 2 )]e 3 (see also footnote f) of Table 3 …”
Section: Crystallography and Linear Optical Propertiesmentioning
confidence: 96%
See 3 more Smart Citations
“…Until now, only some chalcogenides with chalcopyrite structure [24][25][26] and the organic salt potassium trihydrogen di(cis-4-cyclohexene-1,2dicarboxylate) dihydrate [27] were reported to behave correspondingly. As a consequence of the small birefringence, however, phase matching conditions cannot be fulfilled for χ (2) -based frequency conversion processes, such as second harmonic generation or sum frequency generation. Figure 6 (online color at www.lphys.org) Fragments of SRS and RFWM spectra of our crystal of Sr2ZnGe2O7, recorded at room temperature with picosecond pumping at the wavelength λ f 1 = 1.06415 μm in excitation geometry: (a) (e 1 +e 2 )[(-e 1 +e 2 )(-e 1 +e 2 )] (e 1 +e 2 ); (b) e 3 [(-e 1 +e 2 )(-e 1 +e 2 )]e 3 (see also footnote f) of Table 3 …”
Section: Crystallography and Linear Optical Propertiesmentioning
confidence: 96%
“…In the course of our SRS study of the (noncentrosymmetric) crystal of Sr 2 ZnGe 2 O 7 we observed several manifestations of nonlinear-laser χ (2) -and χ (3) -interactions with picosecond pumping either at the fundamental wavelength λ f 1 = 1.06415 μm or at λ f 2 = 0.53207 μm. Among them are multi-wavelength Stokes and anti-Stokes comb generation via SRS and RFWM of more than a sesqui-octave bandwidth, SHG, THG, as well as cascaded χ (2) ↔ χ (3) and χ (3) ↔ χ (3) self-frequency conversion lasing processes in the spectral region of SHG and THG, respectively.…”
Section: Nonlinear-laser Effectsmentioning
confidence: 97%
See 2 more Smart Citations
“…Inherently disordered structures: 7Ln2O3 • 95iO2 where Ln = La or Gd [6], Ca2Ga2SiO7 [7], LaSr2Ga11O20 [8], Sr1-xNdxMgxΑ112_ O19 [9], BaLaGa3O7 [10], SrLaGa307 [11], CaΝdAlO4 [12], SrLaAlO4.…”
mentioning
confidence: 99%